1980
DOI: 10.1002/anie.198009291
|View full text |Cite
|
Sign up to set email alerts
|

“Synthetic Enzymes”. Highly Stereoselective Epoxidation of Chalcone in a Triphasic Toluene‐Water‐Poly[(S)‐alanine] System

Abstract: thus obtainable only as a chloroform solution with 2-4% of (2) and 10-15% of tert-butyl alcohol.Although the hydrocarbon (1) is a highly reactive compound, which polymerizes in condensed phase even at -78"C, its solution in chloroform containing a small amount of hydroquinone can be kept several days at -30 "C. Its spectroscopic resemble those of cyclopropane and cyclopropene. In particular the I3C-H spin-spin coupling constants (158 and 225 Hz) compared to the coupling constants observed for cyclopropane and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(94 citation statements)
references
References 7 publications
2
92
0
Order By: Relevance
“…Weitz±Scheffer epoxidation catalyzed by polymeric amino acids reported by Julia ¬ and Colonna. [73] Table 5. HKR of racemic epichlorhydrin (46) catalyzed by salen complex 45 (for details see Jacobsen et al [77] Figure 14.…”
Section: Ring Opening Of Epoxidesmentioning
confidence: 98%
See 2 more Smart Citations
“…Weitz±Scheffer epoxidation catalyzed by polymeric amino acids reported by Julia ¬ and Colonna. [73] Table 5. HKR of racemic epichlorhydrin (46) catalyzed by salen complex 45 (for details see Jacobsen et al [77] Figure 14.…”
Section: Ring Opening Of Epoxidesmentioning
confidence: 98%
“…The copper complexes of 69a ± 72a and the corresponding monomeric species were used as catalysts in cyclopropanation reactions of substituted styrenes and ethyl diazoacetate (73) to give cis-and trans-2-arylcyclopropanecarboxylic acid ethyl esters (74) (Scheme 10). [41] The cis/trans-ratio depended on the R 1 substituent (Table 12).…”
Section: Cyclopropanation Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Juliá-Colonna epoxidation is one of the first examples of polypeptide-catalyzed reactions in an aqueous system. Thus, excellent enantioselectivities have been obtained using polyamino acid derivatives such as poly-L-alanine or poly-L-leucine in an organic solvent and an aqueous layer containing H 2 O 2 and NaOH [162,163]. However, this transformation has several limitations, such as the narrow substrate scope and the long reaction times.…”
Section: Aqueous Oxidation and Reduction Processes With Supported Orgmentioning
confidence: 99%
“…Catalytic asymmetric epoxidations of allylic alcohols using a Ti-tartrate complex 121,122) and unfunctionalized olefins using salen-manganese complexes 123) are well established. On the other hand, since the initial report by Juliá and coworkers, 124) the catalytic asymmetric epoxidation of enones has been studied using several other methodologies such as ligand-metal catalysts, phase-transfer catalysts, and polyamino acid catalysts. 119,120) Previously, Shibasaki et al reported a general catalytic asymmetric epoxidation of enones using alkali-metal free lanthanide-BINOL complexes.…”
Section: Catalytic Asymmetric Epoxidation 3-1 Catalytic Asymmetric Ementioning
confidence: 99%